The study of vagrants’ moral values in Astana - Issakhanova A. A. (Human and society, 2017)
vagrancy in the modern world has become greater than ever. More and more people become vagrants. They move away from the social reality, can’t cope with the onslaught of globalization and economic instability. Vagrancy problem is considered by many authors, but it does not become less relevant. This article discusses the psychological sense of self well-being of vagrants through moral self-esteem indicators. It also describes the relationship of psychological well-being and personal morality. Personal morality and psychological well-being reflect moral orientation of both separate group or the whole country. Positive values and psychological well-being as a subjective attitude for multinational Kazakhstan are the base in prosperity and stability. Vagrants’ morality manifestations reflect the social development of society at the level of vulnerable social situation, and its development can cause degradation of public consciousness. For this reason, it is important to monitor the level of morality of a multinational society not only in society's views, but also in certain categories of citizens.
Keywords: личность; нравственные ценности; нравственность; психологическое благополучие; Moral; psychological well-being; бродяжничество; person; moral values; vagrancy